Basalt fibre-reinforced concrete: review of fresh and mechanical properties - Bheel, N. (Springer Science and Business Media B.V., 2021)
The use of basalt fibres to improve the hardened properties of concrete has increased in recent times. The incorporation of these fibres into concrete results in a change in the hardened state of concrete. However, these fibres also influence the corresponding fresh properties of concrete, specifically its workability. Therefore, it is critical to understand how the incorporation of basalt fibres influences the fresh and hardened properties of concrete. This review presents a summary of the properties of basalt-fibre reinforced concrete (BFRC) in terms of its fresh and mechanical properties. This review focuses mainly on how the basalt fibre dosage and length affect the properties of BFRC. Â© 2021, The Author(s), under exclusive licence to Springer Nature Switzerland AG part of Springer Nature.